1999
DOI: 10.1038/sj/leu/2401582
|View full text |Cite
|
Sign up to set email alerts
|

True

Abstract: A retrospective analysis of patients presenting with primary lymphoma of bone (PLB) was performed to determine clinical factors affecting prognosis in relation to histological subtype and treatment outcome. Data from 106 patients, presenting with a PLB between 1943 and 1996, were retrieved from the files of the Netherlands Committee on Bone Tumours and Leiden University Medical Centre. The lymphomas were reclassified according to the REAL and updated Kiel classification. The clinical presentation, survival and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, almost any lymphoma histology has been reported causing primary bone disease, including low grade histologies, anaplastic lymphoma [11] and Burkitt lymphoma [12]. Interestingly, the sites of occurrence differ among the various studies: in two series of Japanese patients, PBL most commonly involved the pelvis, [13,14] in others the most common sites of disease were the long bones, [15,16] another study of 131 patients of the British Columbia Cancer Agency reported equal frequency between axial and extremity involvement [17] and finally the SEER database study reported a predominance of axial involvement among 1,500 PBL patients [7], a finding our study shares.…”
Section: Discussionmentioning
confidence: 99%
“…However, almost any lymphoma histology has been reported causing primary bone disease, including low grade histologies, anaplastic lymphoma [11] and Burkitt lymphoma [12]. Interestingly, the sites of occurrence differ among the various studies: in two series of Japanese patients, PBL most commonly involved the pelvis, [13,14] in others the most common sites of disease were the long bones, [15,16] another study of 131 patients of the British Columbia Cancer Agency reported equal frequency between axial and extremity involvement [17] and finally the SEER database study reported a predominance of axial involvement among 1,500 PBL patients [7], a finding our study shares.…”
Section: Discussionmentioning
confidence: 99%